Privacy Preserving Visual Log Service with Temporal Interval Query using Interval Tree-based Searchable Symmetric Encryption - Pham, Viet-An; Hoang, Dinh-Hieu; Chung-Nguyen, Huy-Hoang; Tran, Mai-Khiem; Tran, Minh-Triet (Informatica, 2020)
Visual logs become widely available via personal cameras, visual sensors in smart environments, or surveillance systems. Storing such data in public services is a common convenient solution, but it is essential to devise a mechanism to encrypt such data to protect sensitive information while enabling the capability to query visual content even in encrypted format at the services. More precisely, we need smart systems that their security and practicality must be balanced against each other. As far as we know, in spite of their importance in preserving personal privacy, such reliable systems have not gained sufficient attention from researchers. This motivates our proposal to develop a smart secure service for visual logs with a temporal interval query. In our system, visual log data are analyzed to generate high-level contents, including entities, scenes, and activities happening in visual data. Then our system supports data owners to query these high-level contents from their visual logs at the server-side in a temporal interval while the data are still encrypted. Our searchable symmetric encryption scheme TIQSSE utilizes interval tree structure and we prove that our scheme achieves efficient search and update time while also maintaining all important security properties such as forward privacy, backward privacy, and it does not leak information outside the desired temporal range.